2015
DOI: 10.1074/jbc.m115.676221
|View full text |Cite
|
Sign up to set email alerts
|

Zeta Inhibitory Peptide Disrupts Electrostatic Interactions That Maintain Atypical Protein Kinase C in Its Active Conformation on the Scaffold p62

Abstract: Background: How atypical PKCs are maintained in an active conformation is unknown. Results: We identify an acidic surface on the aPKC scaffold, p62, that tethers the kinase's autoinhibitory pseudosubstrate to allow activity. The biologically active basic peptide, ZIP, competes for binding to this surface, resulting in localized aPKC autoinhibition. Conclusion: p62 tethers aPKCs in an active conformation. Significance: p62 is a molecular target for ZIP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 56 publications
1
39
0
Order By: Relevance
“…On CKAR-PB1 p62 , deletion of the pseudosubstrate significantly enhanced basal activity, revealing some autoinhibition by the pseudosubstrate when PKC is bound to p62. This is consistent with our previous study showing that full-length PKC displays ϳ25% of its maximal unrestrained activity on p62 as assessed with a p62-scaffolded CKAR (6). Deletion of the pseudosubstrate had no significant effect on the activity on the Par6 scaffold, revealing that the majority of the PKC bound to Par6 is in the open conformation, as reported previously (7), with the pseudosubstrate tethered away from the substrate-binding cavity.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…On CKAR-PB1 p62 , deletion of the pseudosubstrate significantly enhanced basal activity, revealing some autoinhibition by the pseudosubstrate when PKC is bound to p62. This is consistent with our previous study showing that full-length PKC displays ϳ25% of its maximal unrestrained activity on p62 as assessed with a p62-scaffolded CKAR (6). Deletion of the pseudosubstrate had no significant effect on the activity on the Par6 scaffold, revealing that the majority of the PKC bound to Par6 is in the open conformation, as reported previously (7), with the pseudosubstrate tethered away from the substrate-binding cavity.…”
Section: Discussionsupporting
confidence: 92%
“…7A). Analysis of FRET as a measure of translocation (described previously (6)) revealed that insulin stimulation caused translocation of both YFP-p62 and YFP-PKC to CFP-IRS-1, in addition to translocation of YFP-PKC to CFP-p62 (Fig. 7B).…”
Section: Scaffold Proteins Differentially Regulate the Phosphorylatiomentioning
confidence: 67%
See 3 more Smart Citations